Serum Tumor Markers As Predictors Of Treatment Response And Survival In Patients With Cervical Cancer: A Comprehensive Systematic Review - Kottagi, Smita; Basalingappa, Basalingappa (Journal of Neonatal Surgery, 2025)
Background: Serum tumor markers have emerged as promising biomarkers for risk stratification and treatment monitoring in cervical cancer, yet their precise clinical utility remains incompletely defined. This systematic review aimed to evaluate the prognostic and predictive value of serum tumor markers for treatment response and survival outcomes in cervical cancer patients. Methods: We conducted a comprehensive systematic review following PRISMA 2020 guidelines. Five databases were searched from inception to December 2024 for studies evaluating serum tumor markers in cervical cancer patients with treatment response or survival outcomes. Study quality was assessed using appropriate risk of bias tools. Data were extracted on marker performance, survival outcomes, and clinical characteristics. Meta-analysis was performed using random-effects models where appropriate. Results: Sixty-eight studies encompassing 12,456 patients were included. The most frequently studied markers were squamous cell carcinoma antigen (SCC-Ag, 42 studies), carcinoembryonic antigen (CEA, 38 studies), cancer antigen 125 (CA-125, 35 studies), and cytokeratin fragment 21-1 (CYFRA 21-1, 18 studies). Pre-treatment elevation of SCC-Ag in squamous cell carcinoma was associated with significantly reduced overall survival (pooled HR: 2.47, 95% CI: 2.12-2.87, p<0.001) and progression-free survival (pooled HR: 2.89, 95% CI: 2.47-3.38, p<0.001). CA-125 demonstrated superior performance in adenocarcinoma patients (overall survival HR: 2.31, 95% CI: 1.89-2.82, p<0.001). All major markers retained independent prognostic significance after adjustment for clinical variables. Marker normalization within 3 months of treatment initiation was associated with improved outcomes across all markers. For recurrence detection, SCC-Ag achieved 78.9% sensitivity and 91.2% specificity in squamous cell carcinoma, while CA-125 showed 73.4% sensitivity and 89.7% specificity in adenocarcinoma. Multi-marker approaches demonstrated superior performance, with combined sensitivity reaching 84-87% for recurrence detection. Conclusions: Serum tumor markers demonstrate significant independent prognostic and predictive value in cervical cancer management. Histology-specific strategies optimize clinical utility, with SCC-Ag preferred for squamous cell carcinoma and CA-125 for adenocarcinoma. These biomarkers enhance risk stratification beyond conventional clinical variables and provide valuable information for treatment response monitoring and post-treatment surveillance. Integration of multi-marker approaches and emerging liquid biopsy technologies offers promising opportunities for personalized cervical cancer management.